(untitled) - Bilal, J. (Manila, 1980)
This project on assessment of oil pollution and its impact on living aquatic resources in East Asia was decided to be started with an inventory of the present situation, i.e. a preparatory phase of getting acquainted,...
Keywords: Environmental protection,Oil pollution of the sea,Bảo vệ môi trường,Ô nhiễm dầu trên biển